Death as Deterrent or Prosecutorial Tool? Examining the Impact of Louisiana’s Child Rape Law - Crews, Angela (2002)
This project measures the impact of a 1995 amendment to Louisiana’s aggravated rape statute that allows juries to consider imposing the death penalty for convicted child rapists. Preamendment populations of cases from two large parishes (counties) were compared to postamendment populations of cases. In addition, 40 individual case files were randomly selected and reviewed. Variables measuring certainty, severity, and swiftness of punishment were compared. The only significant change was the reduction of trials, which may be linked to an increased propensity for plea agreements, dismissals, and charge reductions. In general, offenders initially charged with aggravated rape of a child seemed to benefit from the passage of this amendment, as did district attorneys’ offices. Unfortunately, the state of Louisiana does not seem to be benefiting from the increased deterrence and retribution that this amendment was touted to deliver